Scientific Realism and Anti-Realism Through the Lens of Sunnī Divine Action Models - Jalajel, David Solomon (Theology and science, 2023)
Scientific realism and anti-realism, in various forms, frame many philosophical discussions about what constitutes a successful scientific theory. This paper explores this within an Islamic framework by examining the Sunnī theological tradition's various divine action models (DAMs) for their possible impact upon the theological reception of scientific realism and anti-realism, concluding that the tradition would be committed to an agnostic stance on the question. This enables the tradition to remain relevant to a broad spectrum of future scientific developments and changing intellectual currents.